Effects of Training on Organizational Performance in the Ethiopian Textile Industry: Interview based Investigation using MAXQDA - Metasebia Adula; Shashi Kant; Zerihun Ayenew Birbirsa (iRASD Journal of Management)
Global competitiveness is based on the serious matter of the work attitude of employees because it is dependent on how well companies train their work force. With the advent of technology, it is important to investigate and improve the employee attitude towards work with the inclusion of technological upgrades for humans through training. Training may differ from one organization to the next in the form of on-the-job and off-the-job training. Training paved the way for the type of attitude employees have towards their work. Skill labor's positive view towards work is substructure on advanced training methods that make them differentiate in work place competition. Researchers first make thematic analysis in the form of code data segments with the help of MAXQDA 2020 software. After activation of all inserted interviews, researchers conducted the mixed-method analysis. A single-case analysis was framed for theme identification with the help of thematic analysis. After that, thematic coding was framed for content analysis. For identification, screening, and intent, PRISMA was employed. A coded frequency matrix was assimilated to depict the functionalism of training in the study area in the form of bibliographic analysis. Systematic evaluation of the interview text manifested that training is considered by most employees as the initial point of skill development and an extended part of positive work attitude development, resulting in enhanced organizational performance in textile industries. Study outcomes based on the positivism approach will inform policy recommendations because of its objectivity.